2020
DOI: 10.1186/s13104-020-05352-3
|View full text |Cite
|
Sign up to set email alerts
|

Serum inflammatory and oxidative stress biomarkers levels are associated with pain intensity, pressure pain threshold and quality of life in myofascial pain syndrome

Abstract: Objectives We aimed to determine the serum concentrations of some inflammatory and oxidative stress biomarkers in relation with pain intensity and quality of life in patients with myofascial pain syndrome (MPS) compared to healthy controls. This study is a case–control study. The participants were selected from MPS patients who referred to rehabilitation outpatient clinics of the Tabriz University of Medical Sciences, Iran. Results Serum hs-CRP (4.68 ± 4.36 vs. 2.92 ± 4.55 g/mlµ respectively, p = 0.011), pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Fifth, both the ICTest and DC/TMD of axis I are dichotomous tests, which does not allow them to establish any cut-off points or quantitative results. Finally, the psychological condition of a patient, in terms of stress, exercise habits, or comorbid medical conditions, could influence the patient’s sensitization to pain when performing the test [ 37 , 38 ]. Further investigations into etiology and sociocultural factors, and their potential contribution to taxonomy and diagnosis, are required, particularly within the context of a complex disease such as TMD [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, both the ICTest and DC/TMD of axis I are dichotomous tests, which does not allow them to establish any cut-off points or quantitative results. Finally, the psychological condition of a patient, in terms of stress, exercise habits, or comorbid medical conditions, could influence the patient’s sensitization to pain when performing the test [ 37 , 38 ]. Further investigations into etiology and sociocultural factors, and their potential contribution to taxonomy and diagnosis, are required, particularly within the context of a complex disease such as TMD [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism was described with respect to immunological disturbance, impaired synaptic transmission, pathological microglial activity, and proliferation. The development of opioid tolerance and addiction, opioid hyperalgesia, and cognitive disorders associated with brain plasticity are crucial effects associated with oxidative–antioxidative imbalance [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that agonists of the delta-opioid receptor (DOR) have a neuroprotective effect and lead to an increase in the survivability of neuronal cells. Furthermore, experimental data prove that DOR activation leads to the activation of certain pathways that attenuate oxidative mechanisms and delay the progression of neurodegenerative processes [ 2 , 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 The inflammatory response and injury repair coexist, and the development of MTrPs is accompanied by a high expression of inflammatory factors. 41,42 The unknown role of SPHK1/S1P, however, in the occurrence and development of MTrPs will continue to be explored. In this study, a new approach was adopted to perform saphenous vein catheterization for CEUS examination over traditional contrast agent injection through the tail vein.…”
mentioning
confidence: 99%